# Question #5eee2

##### 1 Answer

I will assume that you are treating

We will solve the first equation for

#x = yab#

Now, substitution into the second equation gives:

#a^2 by + by = a^2 + b^2#

Factor out

#y(a^2 b + b) = a^2 + b^2#

And lastly, divide:

#y = (a^2 + b^2)/(a^2 b + b)#

So there's

#y = x/(ab)#

Substitute into the second equation:

#ax + x/a = a^2 + b^2#

Factor

#x(a + 1/a) = a^2 + b^2#

And lastly, divide to isolate

#x = (a^2 + b^2)/(a + 1/a)#

If we would like, we can rewrite

#x = (a^2 + b^2)/((a^2 + 1)/a)#

And then simplify a bit, just to make the equation a little prettier:

#x = (a^3 + b^2 a)/(a^2 + 1)#